ORGANIZATIONAL TRUST AND ITS EFFECT ON THE DECENTRALIZED WORK OF OFFICIALS IN ORGANIZING AND MANAGING LOCAL CHAMPIONSHIPS AFFILIATED WITH THE IRAQI ATHLETICS FEDERATION - Assist. Prof. Dr. Saba Qays Ghadhban (Proximus Journal Publishing, 2026)
The aim of the study is to identify the stage of both decentralized performance and organizational confidence with through those responsible the decentralized work of officials in organizing and managing local championships affiliated with the Iraqi Athletics Federation from their perspective. The study employed a descriptive approach using a correlational method on a sample of those managing local championships of the Iraqi Athletics Federation, including members , coaches, referees, and the president of the central administrative board, as well as the members and presidents of the subfederations for the sports (2020/2021)
Keywords: Organizational trust; decentralized performance; members and presidents